Smartphone Use, Learner Autonomy, and Social Context in Student Creative Thinking: Peran Smartphone, Kemandirian, dan Lingkungan Sosial dalam Berpikir Kreatif Siswa - Fredi, Yosep; Tegeh, I Made; Agustini, Ketut (Indonesian Journal of Innovation Studies, 2026)
General Background: Creative thinking is a core competence in twenty-first-century education, particularly for lower secondary students navigating intensive digital learning environments. Specific Background: The widespread integration of smartphones in Cambridge-curriculum schools positions digital technology, learner autonomy, parental control, and social context as interrelated factors in students’ creative development. Knowledge Gap: Empirical evidence remains limited regarding how these factors are structurally related and how social context operates as a moderator within digitally mediated learning settings. Aims: This study aims to examine the relationships between smartphone use, parental control, and learner autonomy on students’ creative thinking skills, as well as the moderating role of the social environment. Results: Using an ex-post facto quantitative design and PLS-SEM analysis of data from 67 lower secondary students, the findings show that smartphone use and learner autonomy are positively associated with creative thinking, while parental control shows no significant relationship. The social environment does not moderate the relationships involving smartphone use or parental control, but it negatively moderates the relationship between learner autonomy and creative thinking. Novelty: The study reveals the selective moderating function of the social environment, demonstrating that strong social support may reduce the expression of creativity driven by learner autonomy. Implications: These findings underscore the need for balanced educational strategies that integrate digital technology, self-regulated learning, and calibrated social support to foster creative thinking in secondary education contexts. Highlights • Smartphone use is positively associated with students’ creative thinking skills• Learner autonomy shows a significant positive relationship with creative thinking• Social environment weakens the autonomy–creativity relationship under strong support conditions Keywords Smartphone Use; Learner Autonomy; Creative Thinking Skills; Parental Control; Social Environment